KIAI TAWAKKAL AS ŽIŽEKIAN SUBJECT: READING MUSTOFA BISRI’S GUS JAKFAR IN SLAVOJ ŽIŽEK’S PERSPERCTIVE - Aliyatul Himmah (English Letter Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
The paper examines the spiritual practice of Kiai Tawakkal in Gus Mus’ Gus Jakfar implementing Slavoj Žižek’s theory of subject. The articles which combine these two scientific dimensions needs to be done because there are no similar studies which have been previously conducted. In addition, by using Žižek’s theory, it is expected that readers will be able to understand Sufism from a